2009
DOI: 10.5697/oc.51-1.063
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of environmental pollution on the Algerian west coast using caged mussels Mytilus galloprovincialis:

Abstract: The physical and optical properties of an atmospheric aerosol mixture depend on a number of factors. The relative humidity influences the size of hydroscopic particles and the effective radius of an aerosol mixture. In consequence, values of the aerosol extinction, the aerosol optical thickness and theÅngström coefficient are modified. A similar effect is observed when the aerosol composition changes. A higher content of small aerosol particles causes the effective radius of an aerosol mixture to decrease and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 60 publications
3
27
0
1
Order By: Relevance
“…The Algerian coasts are the ultimate receptacle of pollutants of various origins (Boutiba et al, 2003;Grimes, 2003;Taleb et al, 2007Taleb et al, , 2009Houma et al, 2013;Belkacem et al, 2016). These pollutants not only affect the ecological and biological quality of the environment but also indirectly lead to a devaluation of coastal economic interests.…”
Section: Introductionmentioning
confidence: 99%
“…The Algerian coasts are the ultimate receptacle of pollutants of various origins (Boutiba et al, 2003;Grimes, 2003;Taleb et al, 2007Taleb et al, , 2009Houma et al, 2013;Belkacem et al, 2016). These pollutants not only affect the ecological and biological quality of the environment but also indirectly lead to a devaluation of coastal economic interests.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Taleb et al (2007) showed that neutral red retention (NRR) times in mussels, Mytilus galloprovincialis, collected from an aquaculture farm correlated with their reproductive cycle and, consequently, with condition index. Song et al (2007) also reported decreased NRR times in oysters prior to spawning and related this to gametogenesis or its related metabolism and/or biological functions.…”
Section: Discussionmentioning
confidence: 98%
“…En estudios de campo, Talet et al (2009) mostraron un decrecimiento en retención del rojo neutro en lisosomas de hemocitos en M. galloprovincialis trasplantados a zonas con altos niveles de polución orgánica. Esta misma respuesta ha sido correlacionada con altos niveles de exposición de hidrocarburos policíclicos en M. galloprovincialis y P. perna (Francione et al 2007, Pereira et al 2007, P. viridis (Nicholson y Szefer 2003), y ensayos estáticos con Cu (Nicholson 2003).…”
Section: Discussionunclassified
“…In field studies, Talet et al (2009) observed decreased neutral red retention in lysosomes of M. galloprovincialis transplanted to areas with high levels of organic pollutants. This response has been associated with exposure to high levels of polycyclic hydrocarbons in M. galloprovincialis and P. perna (Francione et al 2007, Pereira et al 2007, P. viridis (Nicholson and Szefer 2003), and static assays with Cu (Nicholson 2003).…”
Section: Discussionmentioning
confidence: 99%